A Changing Landscape: Exploring the Relationship between Clean and Clear Status Policy, Coal Mining, and Deforestation - Widjanarko, Achmad Prabu; Gultom, Yohanna Magdalena Lydia (Institut Pertanian Bogor (IPB University), 2024)
Coal plays a crucial role in energy generation in developing nations and serves as a vital source of power amidst growing energy demands. However, coal mining often acts as a primary driver of deforestation and poses significant environmental challenges. Indonesia, a country with extensive forest areas and a significant coal producer, has implemented a Clean and Clear status policy to address regional and administrative issues related to mining permits. This study aims to assess the impact of this government permit for coal mining in forest areas using the fixed effect panel data method, offering insights into the relationship between coal mining activities and deforestation trends. The analysis focused on the period from 2010 to 2019 and covered 110 regencies in Indonesia, providing a comprehensive understanding of the spatial and temporal dynamics of forest loss. The estimation findings indicated a negative correlation between the areas allocated for coal mining concession permits and forest areas, underscoring the need for stringent regulations and effective land management practices. Therefore, it is recommended that the Clean and Clear status policy not only be applicable during the permit granting phase, but also prioritize post-mining periods to ensure the completion of land reclamation activities.